2010
DOI: 10.1128/jvi.01057-10
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Stability States of Disease-Associated Human Prion Protein Identified by Conformation-Dependent Immunoassay

Abstract: The phenotypic and strain-related properties of human prion diseases are, according to the prion hypothesis, proposed to reside in the physicochemical properties of the conformationally altered, disease-associated isoform of the prion protein (PrP Sc ), which accumulates in the brains of patients suffering from CreutzfeldtJakob disease and related conditions, such as Gerstmann-Straussler-Scheinker disease. Molecular strain typing of human prion diseases has focused extensively on differences in the fragment si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…In this study, the same atypical features were found to characterise PrP Sc from other sporadic human and animal TSEs co-analysed with GSS subtypes, well distinguishable from classical types of PrP Sc found in CJD and scrapie. Indeed, when analysed with similar approaches in previous studies, CJD and classical scrapie didn’t show evidence of being enriched in insoluble and protease sensitive PrP Sc [58], [69]. Furthermore, although PK cleavages other than those at residues 82 and 97 have been reported in sCJD [67], scrapie [70] and H-type BSE [71], in all these instances the glycosylated C-terminus of PrP Sc was always part of the protease resistant core.…”
Section: Discussionmentioning
confidence: 67%
“…In this study, the same atypical features were found to characterise PrP Sc from other sporadic human and animal TSEs co-analysed with GSS subtypes, well distinguishable from classical types of PrP Sc found in CJD and scrapie. Indeed, when analysed with similar approaches in previous studies, CJD and classical scrapie didn’t show evidence of being enriched in insoluble and protease sensitive PrP Sc [58], [69]. Furthermore, although PK cleavages other than those at residues 82 and 97 have been reported in sCJD [67], scrapie [70] and H-type BSE [71], in all these instances the glycosylated C-terminus of PrP Sc was always part of the protease resistant core.…”
Section: Discussionmentioning
confidence: 67%
“…This method allowed us to compare the conformational features of human PrP Sc independently of proteolytic treatment and in addition provided quantitative data on levels of PrP Sc , sPrP Sc , and rPrP Sc [15], [30]. The CDI techniques represent a major improvement over previously used semi-quantitative WB-based methods, the finding that has been independently confirmed by another group [60], [61]. The dissociation and unfolding of PrPSc in a presence of increasing concentration of Gdn HCl can be described as follows: [PrP Sc ] n →[sPrP Sc ] n →iPrP→uPrP, where [PrP Sc ] n are native aggregates of PrP Sc , [sPrP Sc ] n are soluble protease-sensitive oligomers of PrP Sc , iPrP is an intermedite, and uPrP is completely unfolded (denatured) PrP [7], [43], [62].…”
Section: Discussionmentioning
confidence: 90%
“…At variance with experimentally cloned rodent prion strains, however, less numerous and less conclusive data have been obtained with PrP Sc preparations extracted from naturally occurring prion diseases, especially in humans. In the few studies performed to date, sCJD MM1 PrP Sc was shown to be more stable than MM 2C PrP Sc by both CDI and CSA, and MM1 PrP Sc was shown to have a moderately higher stability than vCJD PrP Sc by CDI (32)(33)(34). In the present study, we have carried out the first systematic analysis of PrP Sc conformational stability in a large series of brain samples across the whole spectrum of human sCJD and vCJD prions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a systematic analysis of the conformational stability of PrP Sc aggregates across the spectrum of human prions is still lacking. Previous studies focused on the comparison between sCJD subtypes MM1 and MM2 (31)(32)(33) or between variant CJD (vCJD) and the most common sCJD type MM1 (34). Furthermore, only the unfolding induced by GdnHCl was addressed, whereas the thermostability of PrP Sc has never been explored in CJD.…”
mentioning
confidence: 99%